PENGARUH PENERAPAN SISTEM E-FILING DAN PENGETAHUAN PERPAJAKAN TERHADAP EFISIENSI PELAPORAN SPT WAJIB PAJAK (STUDI EMPIRIS PADA WAJIB PAJAK ORANG PRIBADI DI PT. CALTESYS INDONESIA) - Safura, Evi Karina; Hunein, Hamida (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to determine the effect of the application of the e-filing system and knowledge of taxation on the efficiency of reporting individual taxpayers at the PT Caltesys Indonesia office. This type of research uses quantitative methods. Sampling using the Slovin Formula. The data used in this study are primary data. Data collection techniques with survey techniques, namely distributing questionnaires to employees who work at PT Caltesys Indonesia. The total sample in this study was 75 respondents. The analytical method used is multiple regression with the help of SPSS Version 25. The results of the study prove that simultaneously all independent variables, namely the application of the e-filing system and knowledge of taxation have a significant effect on the efficiency of reporting individual taxpayers. Partially the application of the e-filing system (X1) has no significant effect on the efficiency of reporting tax returns, this occurs because taxpayers do not understand the use of e-filing in reporting their tax returns, which means that even though the e-filing system has been implemented within the company, if not supported by knowledge of the system it will not be efficient. Knowledge of taxation (X2) affects the efficiency of reporting such as, which means that if the knowledge of taxation of human resources in a company is good, the level of efficiency of reporting is also good.